فعالية استخدام منصة "ألف للتعليم" في تعليم اللغة العربية بالمدرسة الرشاد الثانوية الإسلامية بكديري - Arwan Rifa'i (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2026)
This study aims to evaluate the effectiveness of using the ‘Alif’ platform in teaching Arabic at Al-Rashad Islamic Senior High School in Kediri. The research seeks to analyse the impact of this digital platform’s implementation on the process and outcomes of Arabic language instruction. Employing a mixed-method research design, data were collected through classroom observations, interviews with teachers and students, as well as pre- and post-tests to assess language proficiency. The findings revealed a marked improvement in student motivation towards learning, vocabulary acquisition, and Arabic communication skills. The ‘Alif’ platform proved effective in creating an interactive learning environment that supports both self-directed and collaborative learning. Although certain technical challenges arose during implementation, the pedagogical benefits realised outweighed the obstacles encountered. This study concludes that integrating the ‘Alif’ platform into Arabic language instruction at Al-Rashad Islamic Senior High School in Kediri contributes positively to enhancing educational quality and raising student academic achievement.